“Meu pai sangra história” — pós-memória em Metamaus, de Art Spiegelman - Facenda , Kathiane Thaís (2022)
This essay analyzes the postmemory formation of the American writer and comic artist Art Spiegelman, son of Jewish Holocaust survivors and author of the renowned Graphic Novel “Maus — A survivor’s tale” (1986 and 1991). The term postmemory, proposed by Marianne Hirsch during the mid-1990s, refers to the transmission of narratives and memories derived from traumatic events between generations. “MetaMaus — A look inside a modern classic Maus” (2011) is the main source of the research and consists of a series of interviews granted by Spiegelman, between 2006 and 2010, to Hillary Chute, a recognized specialist in comic books. This work consists of documents, photographs by Spiegelman and his family, comix and illustrations produced by the comic artist during his career, accessible to the reader through a system of hyperlinks that link these materials to a DVD attached to the book. In MetaMaus, Maus's creation process and Spiegelman's reflections on his own life trajectory are presented. By allowing his creative process to be glimpsed and reflecting on his past, the comic artist makes it possible to visualize how part of the process of transmission and formation of a postmemory about the Holocaust occurred, which took place since his childhood and accentuated during the process of production of Maus. Therefore, the time frame is between the artist's birth, in 1948, and the publication of MetaMaus, in 2011, having Cultural History and studies about memory as a theoretical-methodological contribution.